Campus Sexual Violence Policies and Popular Media: An Examination of Discourses of Sexual Violence - Ostridge, Lindsay (Université d'Ottawa | University of Ottawa, 2025)
In the last decade there has been considerable attention paid to campus sexual violence in Canada by the media, public and politicians. Recent legislative changes now ensure that universities in some provinces must have a standalone sexual violence policy in place, along with a documented response system. But university campuses are not isolated from their social, political and economic contexts and therefore, campus sexual violence policies, like popular media, reflect the trends and values of a larger society. Currently, there is a lack of critical research examining campus sexual violence discourses in the Canadian context, and this undermines the knowledge of how these policies are created, how they work, and whether they are effective. My dissertation offers a critical contribution to fill this gap in the literature. Through the production of three inter-related and publishable papers, I address two research questions: 1) What common discourses are present in sexual violence policies and popular media; 2) What are the discourses that either reinforce or undermine change? To answer these questions, I conducted a feminist critical discourse analysis on a stand alone sexual violence policy; I conducted interviews and mapped the social relations and institutional texts of one sexual violence creation process (including institutional actors, the internal sphere of the sexual violence policy creation process and the external sphere); and finally, I investigated the world outside the campus environment – where the discourse of white feminism dominates certain texts about sexual violence.
Keywords: Campus sexual violence; Discourse Analysis; Institutional Ethnography; Sexual Violence Prevention; Feminism